Spontaneous subdural hemorrhage in immune-thrombocytopenic purpura with Concomitant liver cirrhosis: a case report - Hayati Firdaus; Ho Hui Lian; Hud Zin; Azizan Nornazirah; Zainal Adwin Zainal Abidin; Sanmugarajah Paramasvaran (ResearchGate, 2016)
Spontaneous subdural hemorrhage (SDH) is an uncommon condition in immune thrombocytopenic purpura with concomitant cirrhotic liver disease. A 61-year- old lady presented with worsening headache and acute dizziness with no evidence of trauma. Her clinical examination was uneventful except for minimal purpuric spots at previous phlebotomy sites. Full blood count revealed platelet of 65,000/mm 3 . Computed tomography (CT) of brain revealed crescent-shaped hypodense lesion at left parietal region and at right frontoparietal region, suggestive of chronic SDH. She underwent emergency burr hole to evacuate the clot on the left subdural space. Repeat CT scan after a week revealed a worsening acute-on- chronic SDH on the right parietal region with a residual chronic SDH on the left side. Thus, another burr hole and evacuation of the clots was performed and she had an unremarkable postoperative recovery. She was discharged with tablet prednisolone 0.5 mg/kg (45 mg once a day) was tapered down 5 mg every 2 weeks until she consumed 5 mg per day. Repeat CT scan after a week showed remission of SDH.